2008
DOI: 10.1097/spv.0b013e3181907870
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Muscle Dysfunction

Abstract: Pelvic floor muscle dysfunction is a problem that affects women of all ages. The disorder can present as chronic pelvic pain, dyspareunia, rectal pain, chronic constipation, lower back pain, and a wide array of other complaints. As a result of the various presenting symptoms, patients with pelvic floor muscle dysfunction are seen by a variety of health care workers, including obstetrician-gynecologists, urogynecologists, urologists, colorectal surgeons, orthopedic surgeons, physical therapists, chiropractors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Through these mechanisms, SNM could achieve clinical therapeutic goals for IC/BPS . According to the literature, hypertonic pelvic floor muscle dysfunction is present in approximately 85% of IC /BPS patients . The data in this study showed that the effectiveness rate of SNM for the treatment of IC /BPS was 72.4%.…”
Section: Discussionmentioning
confidence: 62%
“…Through these mechanisms, SNM could achieve clinical therapeutic goals for IC/BPS . According to the literature, hypertonic pelvic floor muscle dysfunction is present in approximately 85% of IC /BPS patients . The data in this study showed that the effectiveness rate of SNM for the treatment of IC /BPS was 72.4%.…”
Section: Discussionmentioning
confidence: 62%
“…The magnitude of the EIH effect has recently been shown to be diminished when evaluated after a CPM paradigm (Gajsar et al, 2018) which may have influenced the possibility to detect EIH in the current study. Furthermore, it is unknown if patients have a similar EIH response, as the majority of research has been on healthy individuals (Koltyn.F, 2000). Chronic pain patients demonstrate increased pain sensitivity which has also been associated with an inefficient EIH (Vaegter, Handberg, & Graven-Nielsen, 2016).…”
Section: Exercise-induced Hypoalgesiamentioning
confidence: 99%
“…PFD is common, affecting 24% to 33% of women (1,2). Pregnancy, menopause, trauma, pelvic surgery, obesity, and systemic diseases have been suggested as inciting events or conditions that contribute to PFD (3). …”
Section: Introductionmentioning
confidence: 99%